Peran Media Massa dalam Meningkatkan Self-Awareness Masyarakat terhadap Pentingnya Vaksinasi Covid-19 di Kabupaten Sidoarjo - Hana Nabilah Santoso; Nikmah Hadiati Salisah (Jurnal Ilmu Komunikasi, 2021)
Some people in Sidorajo Regency are still unsure about the Covid-19 vaccination. This is due to the widespread information on vaccination programs that confuses the public, people feel doubtful and do not care about the vaccination program. Therefore, the Covid-19 vaccination program in the Sidoarjo Regency has not yet reached the specified target. This study will explain how the role of the mass media in increasing the self-awareness of the people of Sidoarjo on the importance of the Covid-19 vaccination. The research method used is qualitative. The results showed that the role of the mass media are: 1) As a window of information, mass media providing a lot of knowledge to the people of Sidoarjo through various media partners. 2) As a reflection of reality, mass media partners of Sidoarjo Regency Government present the latest information related to Covid-19 information in the field. 3) As a filter, mass media capture hoax information circulating in Sidoarjo. 4) As a guide, the mass media direct the correct information if the public is confused. 5) As a forum, Sidoarjo's media partner become a forum for the community to provide feedback on the information received. 6) As a communication partner, mass media of Sidoarjo partners are a place to submit statements or questions.